Liquidity constraints and the permanent income hypothesis: Pseudo panel estimation with German consumption survey data - Martin Beznoska; Richard Ochmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper empirically investigates the relevance of liquidity constraints and excess sensitivity in intertemporal household consumption. Using a pseudo panel that has been constructed on rich German consumption survey data, we estimate the consumption responses to permanent and transitory income shocks, as well as the presence of excess sensitivity to anticipated income changes. A switching regression approach with unknown sample separation is applied to identify the two regimes whether to be liquidity constrained or not. The results are used to test whether liquidity constraints affect the validity of the permanent income hypothesis. For households in the constrained regime, reactions to changes in transitory income are found to be significantly greater than for households in the unconstrained regime. Furthermore, we provide evidence for excess sensitivity to anticipated income changes for households in the constrained regime if total consumption, durable as well as non-durable, is considered.
Keywords: C34; D91; E21; 330; Liquidity constraints; excess sensitivity; household consumption; switching regression; permanent income hypothesis